The Eksploitasi Anak dalam Tradisi Pacuan Kuda Pada Masyarakat Dompu - Akbar Tanjung Juraid; Oryza Pneumatica Inderasari; Khalifatul Syuhada (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2021)
The problem studied in this study is the exploitation of children in the tradition of horse racing in the Dompu community. The purpose of this study is to find out the form of expolocitation of children who act as child jockeys in community traditions in Dompu Regency, knowing the implications of parental parenting on the choice of being a child jockey in Dompu regency and knowing the potential implementation of child protection based on Law No. 35 of 2014 on child jockeys. This research uses a qualitative descriptive approach. The data collection techniques used are methods of observation, in-depth interviews and documentation. Analysis of data in this study in the form of narratives obtained during interview activities, as well as some documents related to research topics. Using the paradigm in social definition, with the theory used in this study is the social theory of Max Weber. The results of this study found that (1). A form of child exploitation that acts as a child jockey in the community tradition in Dompu Regency. Consisting of parental coercion, the risk of accidents of child jockeys, safety and health are threatened, educational challenges and an environment that is not conducive (2). Implications of parental parenting on the choice of being a child jockey in Dompu Regency. Consists of parenting models, family economic resources and hereditary habits (3). The potential implementation of child protection under Law number 35 of 2014 on child jockeys. Consisting of a system of resusing and protecting the use of child jockeys, government regulations related to the use of children as child jockeys and horse racing are used as tourism promotion sectors of Dompu Regency, becoming a characteristic of the Dompu Regency area.